Fostering Effective Teaching Practices: Integrating Formative Assessment and Mentorship in Indonesian Preservice Teacher Education - Entika Fani Prastikawati; Moses Adeleke Adeoye; John Charles Ryan (Indonesian Journal on Learning and Advanced Education (IJOLAE), 2024)
The paper explores the implementation and effectiveness of formative assessment strategies to decorate the mastery of teaching competencies among preservice teachers in Indonesia. It specializes in the role of mentoring in guiding and helping preservice teachers efficiently make use of formative assessment practices to improve their instructional techniques and learner studying results. The study investigates the demanding situations and opportunities encountered in integrating formative assessment into the teacher education curriculum and offers guidelines for enhancing the mentorship system. The research method uses a systematic literature review incorporating the evaluation synthesis and guidance for mentors in enhancing the skills and knowledge of future educators in the context of formative assessment. The findings of the current study are exemplified through an analysis of the several facets of formative assessment and its advantages in enhancing teaching and students' acquisition of knowledge. The findings also offer precious insights for teachers, mentors, and policymakers seeking to elevate the best of teacher education packages and continuous professional improvement amongst preservice teachers by guiding them on the rigorous theories and procedures of formative assessment. This study provides a summary of the theoretical contributions and a step-by-step process for implementing formative assessment. It also discusses the implications of formative assessment for assessment education policies and practices in Indonesia.